Wordplay in the Spongebob movie and its translation in Russian - Muhammad, Asmitazkirah Abdullah (Язык и культура : сборник статей XXXIII Международной научной конференции (16-17 ноября 2023 г.))
This research dealt with three objectives to describe: 1) the types of wordplay, 2) the translation techniques used for wordplay, and 3) the degree of translation equivalence in SpongeBob movie. The findings of the research showed that the translators primarily focused on conveying the intended meaning of the wordplays, while accommodating the unique characteristics and preferences of the Russian language and culture.